2022
DOI: 10.1016/j.gim.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and concerns of patients considering participation in an implementation study of a hereditary cancer risk assessment program in diverse primary care settings

Abstract: Understanding the motivations and concerns of patients from diverse populations regarding participation in implementation research provides the needed evidence about how to design and conduct studies for facilitating access to genetics services. Within a hereditary cancer screening study assessing a multifaceted intervention, we examined primary care patients' motivations and concerns about participation. Methods: We surveyed and interviewed study participants after they enrolled, surveyed those who did not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…This cross-sectional survey found that males were less likely to receive a recommendation for genetic testing and less likely to complete genetic testing than females adjusting for con-founders and cancer type, similar to Vysotskaia et al [23]. Additionally, consistent with prior research, clinician recommendation strongly associated with completing genetic testing amongst both sexes [4,8,23,31].…”
Section: Discussionsupporting
confidence: 79%
“…This cross-sectional survey found that males were less likely to receive a recommendation for genetic testing and less likely to complete genetic testing than females adjusting for con-founders and cancer type, similar to Vysotskaia et al [23]. Additionally, consistent with prior research, clinician recommendation strongly associated with completing genetic testing amongst both sexes [4,8,23,31].…”
Section: Discussionsupporting
confidence: 79%
“…20 The NCCN guidelines were also expanded because patients wish to know if they carry PGVs. 21 In the primary care clinic setting, Duenas et al 21 reported that surveyed patients wished to have testing to learn of their future risk (81%), particularly if the information might help family members (58%) and advance research (34%). In fact, Halverson et al 22 reported that 67% of patients who initially declined testing at the time of the initial evaluation said either they would or had changed their mind about testing if/when the clinicians "mentioned it again.…”
Section: Evidence Supporting the Expanded Guidelinesmentioning
confidence: 99%